Character Development and Morality: In-Depth Analysis of the Animated Film “Encanto” - Pertiwi Gunawan, Felicia; Nurkhamidah, Neni (PRIMACY Journal of English Education and Literacy, 2024)
In this paper, the concept of analyzing film is directed in order to know the character development progress and morality of the story. Analyzing film can enhanced the knowledge given implicitly in the film’s story and the morality behind it. The film analyzed here is “Encanto”. The approach of “Encanto” was simply an attempt to go further into learning about the character’s hidden conception. Each character in the story were highlighted due to the interest of acknowledging every character’s development throughout the storyline and what kind morality represents each of them. The results over the character’s development are divided into the form of themes, such as Acceptance, Self-Worth, and Resilience. From these results, the research can be converted into a conclusion of which themes that’s dominantly relevant throughout the story and the rest of the plot. The highlight will also mention the result of which category of characteristics is the most appealing and what is the overall morality tale of “Encanto” as an animated film.